2015
DOI: 10.1038/nchem.2224
|View full text |Cite
|
Sign up to set email alerts
|

Chemical tagging and customizing of cellular chromatin states using ultrafast trans-splicing inteins

Abstract: Post-translational modification of the histone proteins in chromatin plays a central role in epigenetic control of DNA-templated processes in eukaryotic cells. Developing methods that enable the structure of histones to be manipulated is therefore essential to understand the biochemical mechanisms underlying genomic regulation. Here we present a synthetic biology method to engineer histones bearing site-specific modifications on cellular chromatin using protein trans-splicing. We genetically fused the N-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
140
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(144 citation statements)
references
References 46 publications
1
140
0
3
Order By: Relevance
“…We confirmed the importance of these residues for endogenous hDot1L activity in isolated nuclei through monitoring H3K79 methylation levels subsequent to the site-specific incorporation of a ubiquitin mutant, lacking these residues, into chromatin (26). Extending our findings to other well-established H2B-Ub processes, we find that this ubiquitin hotspot is also necessary for the stimulation of ySet1-mediated H3K4 methylation.…”
Section: Significancesupporting
confidence: 69%
See 1 more Smart Citation
“…We confirmed the importance of these residues for endogenous hDot1L activity in isolated nuclei through monitoring H3K79 methylation levels subsequent to the site-specific incorporation of a ubiquitin mutant, lacking these residues, into chromatin (26). Extending our findings to other well-established H2B-Ub processes, we find that this ubiquitin hotspot is also necessary for the stimulation of ySet1-mediated H3K4 methylation.…”
Section: Significancesupporting
confidence: 69%
“…This approach uses naturally split inteins [referred to herein as the N-terminal intein (Int N ) and C-terminal intein (Int C )] to assemble the desired H2B-Ub construct through an in nucleo protein ligation procedure (SI Appendix, Fig. S11A) (26). This reaction results in attachment of ubiquitin to H2BK120 through an isopeptide linkage that is identical to that used in our in vitro studies and, importantly, without mutating any of the other histones.…”
Section: The Leu71/leu73 Patch Is Required For Hdot1l Stimulation Onmentioning
confidence: 99%
“…We demonstrated that the Cfa GEP intein improves the scope of two such applications: protein cyclization and the in nucleo semisynthesis of chemically tailored chromatin (22,25). The improved cyclization enabled by Cfa GEP may be further extended to a SICLOPPS library and selection system to identify cyclic peptides that bind or inhibit a target enzyme (23).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, split inteins have been used to chemically modify cellular chromatin (25). This in nucleo protein semisynthesis strategy provides a means to validate in vitro observations of histone biochemistry in the context of a native cellular chromatin (26).…”
Section: Resultsmentioning
confidence: 99%
“…Deoxynucleotide analogues are used to chemically modify DNA, which thereby becomes site-specifically photoreactive. Moreover, the availability of reconstituted nucleosomes and their semi-synthetic variants bearing specific chemical modifications has enabled the generation of large nucleosome libraries for analytical experiments on binding properties (Montel et al, 2007;Simon, 2010;Maltby et al, 2012;Pichler et al, 2012;Yun et al, 2012;Lee et al, 2013;Rogge et al, 2013;Al-Ani et al, 2014b;David et al, 2015). The EMBO Journal Mechanisms of nucleosome recognition Valentina Speranzini et al the nucleosome is formed by an octamer of tightly associated histone proteins (H2A-H2B) 2 (H3-H4) 2 , and~150 bp of DNA wrapped around the octamer to define a left-handed superhelical fragment (Luger et al, 1997), where the core of the histone proteins is well defined, while the tails mostly lack a defined structure.…”
Section: Chemical Probes and Nucleosome Librariesmentioning
confidence: 99%